Aspergillus flavus endocarditis in an immunocompetent child. Case report (2018)
Fungal endocarditis (FE) is a rare infection in pediatrics which accounts for 5% of the cases of infective endocarditis. This pathology affects immunosuppressed patients in a greater proportion. We present an immunocompetent 7- year-old female with a history of multiple cardiac surgeries who developed fungal endocarditis due to Aspergillus flavus. The histology study showed liquefactive necrosis and septate hyphae of Aspergillus sp type. The clinical outcome was favorable and the ambulatory follow-up after 12 months showed no new complications.